2014
DOI: 10.1007/s00167-014-2864-1
|View full text |Cite
|
Sign up to set email alerts
|

Can the tibial slope be measured on lateral knee radiographs?

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 29 publications
3
104
0
2
Order By: Relevance
“…However, Akamatsu et al used nearly full length scans, in addition to short radiographs of the joint space, which included the majority of the tibia and enabled a more accurate determination of tibial slope [24]. Our results were consistent with those of Akamatsu et al for short radiographs [18].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, Akamatsu et al used nearly full length scans, in addition to short radiographs of the joint space, which included the majority of the tibia and enabled a more accurate determination of tibial slope [24]. Our results were consistent with those of Akamatsu et al for short radiographs [18].…”
Section: Discussionsupporting
confidence: 87%
“…The methods prescribed by Hashemi et al [11] referenced the mid-shaft of the tibia which is a function of the scan length of the MRI [24], while the novel 3D method referenced the most anterior point of the tibial tuberosity. Definition of the diaphyseal axis of the tibia inherently introduces error and may therefore yield inconsistent data [26] in a 2D approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, long lateral knee radiographs should be preferred over short radiographs. 16 If MRI is used, the circle method described by Hudek et al 26 may be the preferred method since it has been shown to be the most repeatable method. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Dazu wurden die Resektionsebenen am Femur 90°zur mechanischen Femurachse und an der Tibia 90°zur mechanischen Tibiaachse geplant. Der tibiale Slope wurde auf langen lateralen Röntgenaufnahmen als Winkel zwischen der Tangente des medialen und lateralen Tibiaplateaus und der diaphysären Mittelpunkte 5 und 15 cm unterhalb des Tibiaplateaus gemessen [16,17]. Alle Operationen wurden durch 1 Operateur (C. P.) durchgeführt.…”
Section: Op-technikunclassified